PROFIL PRODUKTIVITAS KEPALA SMA NEGERI DI JAKARTA DAN FOKUS PEMBENAHANNYA - Ruknan Ruknan (Lembaga Penelitian UM Metro, 2017)
The objective of the research was to obtain facts about the principals productivity of senior high school state in Jakarta. The research was conducted in the working area of Jakarta Education and Culture Department. Study time from January to March 2015. The design of this study used survey method. The data collection tool in the form of a questionnaire is prepared using a Likert scale. The number of samples determined by using Slovin formula obtained as many as 60 people. The sample was obtained by simple random sampling technique. The results were analyzed using descriptive statistical techniques. The result of the research can be concluded that: First, headmaster's productivity profile of senior high school state in Jakarta based on 25 predictor component that has reached good category as much as 18 pieces or equal to 72%.Secondly, the predictor component of headmaster productivity of senior high school state in Jakarta which is categorized requires correction of 7 units or 28%.